The Effects of a Home-Based Intervention for Young Children with Developmental Delays in Vietnam: 6-Month Follow-Up Results - Jin Y Shin; Son Nguyen Duc; Michael Accardo; Charles Dill (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
We assessed the long-term efficacy of a home-based intervention program for young children (n = 46, ages ranging from 3 to 6 years) with developmental delays in Vietnam. The current paper reports on the six-month follow-up evaluation of the children after their six-month intervention ended. At the same time, the children who were in a wait-list control group during the initial intervention program obtained the same intervention for these six months and their outcomes are reported in this paper. It was hypothesized that after completing the intervention program, the children would retain their adaptive functioning during the six-month follow-up period.